Enhancement adsorption of hexavalent chromium onto modified fly ash from aqueous solution; optimization; isotherm, kinetic and thermodynamic study. Issue 8 (3rd August 2019) - Jahangiri, Katayoun; Yousefi, Nader; Ghadiri, Seid Kamal; Fekri, Rana; Bagheri, Amin; Talebi, Seyedeh Solmaz
Abstract: Fly ash were successfully modified by a chemical method (iron and aluminum salts and surfactant) with the aim of removing Cr(VI) from aqueous solution. In this study, response surface methodology (RSM) and central composite design (CCD) were applied to improve the prediction models and optimize the chromium adsorption parameters. The results disclosed that surfactant-modified fly ash (SMF) had further influence on the fly ash. The predicted values showed that the quadratic model were in good agreement with the predicting values (high regression coefficient (R 2 >0.96), insignificant lack of fit (0.448), high F-value and low P-value (<0.05)). The optimized adsorption parameters were adsorbent dose of 3.53 g/L, initial Cr (VI) concentration of 35.40 mg/L; contact time of 69.32 min and pH of 2.77. The experimental data was described well with Freundlich isotherm (R 2  = 0. 98) and pseudo-second-order kinetic model (R 2  = 0. 99). The results of thermodynamic study represented that the adsorption process was spontaneous, exothermic and chemisorption (free energy (ΔG)= −30 to −40 kJ/mol and standard enthalpy (ΔH)= −41.01 kJ/mol). Therefore, cheap, ease of modification and high efficiency of fly ash has been recommended a great promise for reducing the chromium from aqueous solution. Graphical Abstract: